2014
DOI: 10.6061/clinics/2014(07)07
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between intra-abdominal pressure and pulmonary volumes after superior and inferior abdominal surgery

Abstract: OBJECTIVE:Patients undergoing abdominal surgery are at risk for pulmonary complications. The principal cause of postoperative pulmonary complications is a significant reduction in pulmonary volumes (FEV1 and FVC) to approximately 65-70% of the predicted value. Another frequent occurrence after abdominal surgery is increased intra-abdominal pressure. The aim of this study was to correlate changes in pulmonary volumes with the values of intra-abdominal pressure after abdominal surgery, according to the surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
12
0
2
Order By: Relevance
“…This may be due to both groups were had resemble characteristic and functionally comparable to each other. The present result is similar to a study conducted by (13,14) are similar with the result of present study, and the pulmonary function test parameters did not differ between two groups before operation. After the application of the breathing exercise pursed lip methods through the present study, the results indicated that there is an improvement in the case group lungs volumes compared with those patients in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to both groups were had resemble characteristic and functionally comparable to each other. The present result is similar to a study conducted by (13,14) are similar with the result of present study, and the pulmonary function test parameters did not differ between two groups before operation. After the application of the breathing exercise pursed lip methods through the present study, the results indicated that there is an improvement in the case group lungs volumes compared with those patients in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…There is substantial evidence to prove that DM1 patients show abnormalities with regard to the ventilator control mechanisms, and their conditions became more critical when exposed to anaesthetic agents, resulting in a low central respiratory drive 14 , 15 . Furthermore, this hypothesis can be consolidated by our result in which 9 of 11 patients received abdominal surgery, which is an important risk factor of hypoventilation 16 .…”
Section: Discussionmentioning
confidence: 61%
“…There is substantial evidence to prove that DM1 patients show abnormalities with regard to the ventilator control mechanisms, and their conditions became more critical when exposed to anaesthetic agents, resulting in a low central respiratory drive 14,15 . Furthermore, this hypothesis can be consolidated by our result in which 9 of 11 patients received abdominal surgery, which is an important risk factor of hypoventilation 16 . www.nature.com/scientificreports/ www.nature.com/scientificreports/ The concerns regarding increase in the risk of defects in the cardiac rhythm conduction and potential progression of known conduction delays in patients with DM1 during the perioperative period are evident 17 .…”
Section: Discussionmentioning
confidence: 61%
“…Breathing exercises were part of the protocol of two studies (26,27) of this review, and another study (22) focused on guidelines for performing correct breathing during exercises to strengthen the AP. According to De Cleva et al (39) , lower abdominal surgery is associated with a 10 to 15% decrease in functional residual capacity. Recent study (40) demonstrated that respiratory physiotherapy plays an important role in improving vital capacity (VC) in patients undergoing abdominal surgery, being performed breathing exercises associated with upper limb exercises and assisted coughing, in addition to lower limb exercises, ending with the use of intermittent positive pressure or incentive spirometer, depending on the group, and both groups obtained positive results.…”
Section: Discussionmentioning
confidence: 99%